The effectiveness of sports advertising and its impact on the consumer - saadsaoud, Fouad (sports creativity, 2025)
Advertising has emerged as a specialized communication process in our current era, with modern and sophisticated manifestations, unlike its early beginnings. It has moved from traditional forms that were limited to informative content to its current highly influential forms and complex system of effects, suggestions, and persuasive techniques, benefiting from modern technology and the development of persuasion methods and their various applications in mass communication. Sports communication is one of the mass communication methods used in this field – as an advertising tool – but today the consumer exposed to advertising in stadiums or outside them (the fan of his team) finds himself facing multiple products, both national and foreign, in fierce competition and with a large volume of advertising messages.